Lost in the claws at Linda Animal Clinic and Surgery - Mokhtar, Norsyahida (IIUM Press, 2024)
This case presents the operational challenges faced by Linda Animal Clinic & Surgery following a period of initial slow growth which transitioned into increasing demand. The sudden departure of Dr. Alice amid these challenges further strained the clinic’s performance. In response, the clinic turned to offering more ancillary services.